Reduced solar radiation limits phenolic compounds accumulation and extends anthocyanin synthesis in colored hull-less barley grains - Iván Friero; Mariona Martínez-Subirà; Alba Macià; María-Paz Romero; Ignacio Romagosa; Marian Moralejo (Journal of Agriculture and Food Research, 2025)
Barley is a rich source of phenolic compounds (PCs), whose accumulation is strongly influenced by environmental conditions, directly affecting grain nutritional quality. This study investigated the effects of shading during grain filling on PCs synthesis in three hull-less barley genotypes with different grain colors: yellow (DHL-180868), purple (DHL-151340), and black (DHL-191250). Field experiments were conducted over two seasons, applying shading treatments either for 15 days after heading (T1) or continuously until harvest (T2). Shading significantly reduced thousand grain weight (TGW) in the purple and black grain genotypes, while the yellow genotype remained unaffected, suggesting greater adaptability to low-solar radiation. TGW reductions reached up to 14 %, highlighting genotype-specific sensitivity to shading. Total PCs content also decreased under shading across all genotypes, with T1 and T2 having similar effects, with reductions of up to 21 %, emphasizing the critical role of early grain development in PCs synthesis. Despite this overall decline, individual compounds exhibited distinct responses. Notably, in DHL-151340, prolonged shading delayed anthocyanin synthesis resulting in higher final concentrations, exceeding unshaded levels by more than 40 %. Principal component analysis identified environmental factors as the main drivers of PCs variability, with free PCs more abundant in 2023 and bound PCs in 2024. These findings highlight the complex interplay between genotype and solar radiation availability in PCs accumulation and suggest that controlled shading could be a viable strategy to enhance specific bioactive compounds in barley. This research provides valuable insights for barley breeding programs and agronomic practices aimed at optimizing its functional food potential.